2021
DOI: 10.3390/met11060943
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Effect and Superelasticity of [001]-Oriented FeNiCoAlNb Single Crystals Aged under and without Stress

Abstract: The two-step ageing of Fe-28Ni-17Co-11.5Al-2.5Nb (at. %) single crystals under and without stress, leads to the precipitation of the γ′- and β-phase particles. Research has shown that γ–α′ thermoelastic martensitic transformation (MT), with shape memory effect (SME) and superelasticity (SE), develops in the [001]-oriented crystals under tension. SE was observed within the range from the temperature of the start of MT upon cooling Ms, to the temperature of the end of the reverse MT upon heating Af, and at tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Recently, FeNiCoAlXB (X: Ta, Nb, Ti) alloys have been reported to have greater than 4% superelastic strain [1-3] and 1.6% shape memory strain [4], and single crystals have exhibited at least a 5% recoverable strain [5][6][7][8]. The martensitic transformation (MT) of the FeNiCoAlXB (X: Ta, Nb, Ti) alloy system is face-centered cubic (fcc) (austenite) to bodycentered tetragonal (bct) (martensite).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, FeNiCoAlXB (X: Ta, Nb, Ti) alloys have been reported to have greater than 4% superelastic strain [1-3] and 1.6% shape memory strain [4], and single crystals have exhibited at least a 5% recoverable strain [5][6][7][8]. The martensitic transformation (MT) of the FeNiCoAlXB (X: Ta, Nb, Ti) alloy system is face-centered cubic (fcc) (austenite) to bodycentered tetragonal (bct) (martensite).…”
Section: Introductionmentioning
confidence: 99%
“…Previous aging heat-treatment studies of FeNiCoAlXB (X: Ta, Nb, Ti) alloys have reported that the optical aging temperatures of these alloys, to obtain superelastic properties, ranged from 600 to 700 • C [1][2][3][4][5][6][7][8]. Tanaka et al [1] found that Fe 40.95 Ni 28 Co 17 Al 11.5 Ta 2.5 B 0.05 (at.%) alloys aged at 600 • C for 72 h show a 13.5% superelastic strain at room temperature, and the diameter of the precipitate was 3 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tseng et al [23] found that using Ti to replace Ta could reduce the aging heat treatment times. A FeNiCoAlTi single crystal with <100> orientation aged at 600 • C for 4 h possessed 6% superelastic strain when the test temperature was at −80 • C. Chumlyakov et al [36][37][38] showed that adding Nb to this alloy could increase the hardness of the austenite matrix and improve their superelastic properties. FeNiCoAlNb single crystals with <100> orientation in two-step aging (700 • C-0.5 h + 700 • C-3 h) demonstrated 7% superelastic strain in tension and 13.5% in compression.…”
Section: Introductionmentioning
confidence: 99%
“…FeNiCoAlNb single crystals with <100> orientation in two-step aging (700 • C-0.5 h + 700 • C-3 h) demonstrated 7% superelastic strain in tension and 13.5% in compression. The precipitates size ranged from 5 to 8 nm [38].…”
Section: Introductionmentioning
confidence: 99%